Menelisik Relevansi Pancasila Sebagai Spiritualitas Hidup Bangsa Indonesia Yang Majemuk - Bartolomeus Samho; Rudi Setiawan (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2022)
Pancasila is the spirituality that animates the life of the Indonesian nation. This paper aims to describe Pancasila as the spirituality of life for the Indonesian people. Based on the results of research in 2015 entitled "Articulating Pancasila as the spirituality of the pluralistic life of the Indonesian nation: a philosophical study", the researchers affirm and promote the relevance of Pancasila as the spirituality of the Indonesian people's life. The research method used in this paper is qualitative with a heuristic and hermeneutics approach. The results or findings of this study indicate that Pancasila originates from the culture of the Indonesian nation. It is an extract or crystallization of cultural values that are life principles of the Indonesian people. Therefore, the articulation of Pancasila as the spirituality of the Indonesian people's life seems relevant. The benefit of this research is to broaden the horizons of Pancasila in the life of the Indonesian people. In addition, this research is also useful for strengthening the commitment of the Indonesian people in implementing, affirming, and promoting the values of Pancasila in the practice of life.